2019
DOI: 10.3847/1538-4365/ab22a8
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Binary Luminosity Function Scaling Relations for Local Galaxies Based on Subgalactic Modeling

Abstract: We present new Chandra constraints on the X-ray luminosity functions (XLFs) of X-ray binary (XRB) populations, and their scaling relations, for a sample of 38 nearby galaxies (D = 3.4-29 Mpc). Our galaxy sample is drawn primarily from the Spitzer infrared nearby galaxy survey (SINGS), and contains a wealth of Chandra (5.8 Ms total) and multiwavelength data, allowing for star-formation rates (SFRs) and stellar masses (M ⋆ ) to be measured on subgalactic scales. We divided the 2478 X-ray detected sources into 21… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
204
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(225 citation statements)
references
References 124 publications
(156 reference statements)
21
204
0
Order By: Relevance
“…Thus the Mineo et al (2012a) XLF could be underestimating the probability of finding a HMXB in this population of galaxies. Lehmer et al (2019) observes this enhancement in 4 dwarf galaxies of similar masses and metallicities to those in our sample. We follow the same procedure outlined earlier in the paragraph but use the normalisations outlined in Lehmer et al (2019) and observe some increase in the probability of finding a HMXB at any given X-ray luminosity.…”
Section: Completeness-corrected Luminosity and Accretion Rate Distribsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus the Mineo et al (2012a) XLF could be underestimating the probability of finding a HMXB in this population of galaxies. Lehmer et al (2019) observes this enhancement in 4 dwarf galaxies of similar masses and metallicities to those in our sample. We follow the same procedure outlined earlier in the paragraph but use the normalisations outlined in Lehmer et al (2019) and observe some increase in the probability of finding a HMXB at any given X-ray luminosity.…”
Section: Completeness-corrected Luminosity and Accretion Rate Distribsupporting
confidence: 87%
“…Lehmer et al (2019) observes this enhancement in 4 dwarf galaxies of similar masses and metallicities to those in our sample. We follow the same procedure outlined earlier in the paragraph but use the normalisations outlined in Lehmer et al (2019) and observe some increase in the probability of finding a HMXB at any given X-ray luminosity. We have not shown this relationship on figure 9 because the small sample size means the relationship will have large and undefined uncertainties and believe plotting the relationship would appear overly definitive.…”
Section: Completeness-corrected Luminosity and Accretion Rate Distribsupporting
confidence: 87%
“…Recent work has shown that the galaxy-to-galaxy scatter from these relations may be due to physical differences between the galaxies, i.e. stellar ages (Fragos et al 2008;Lehmer et al 2017Lehmer et al , 2019 or metallicity (Fragos et al 2013;Basu-Zych et al 2013a;Douna et al 2015;Brorby et al 2016;Lehmer et al 2016), yet this level of detail is beyond the scope of this paper and does not affect the overall predictions. However, our estimates indicate that the 4-year eROSITA survey will detect sufficient numbers of galaxies to allow detailed investigation of X-ray emission as a function of e.g.…”
Section: Resultsmentioning
confidence: 87%
“…In practice, galaxy-to-galaxy variations from these scaling relations can be quite large, and have been shown to vary systematically with second-order galaxy properties such as metallicity and stellar age (e.g. Basu-Zych et al 2013a,b;Douna et al 2015;Brorby et al 2016;Lehmer et al 2016Lehmer et al , 2017Lehmer et al , 2019. In this section we explore the effect of scatter from the above scaling relations on our predictions of whether a galaxy can be detected.…”
Section: Effects Of Scatter On ''Detectability''mentioning
confidence: 95%
“…As an additional step in the analysis of the true nature of the secondary point source, we compare the hard X-ray luminosity to the total, expected X-ray luminosity due to XRBs. Following a similar analysis to Foord et al (2017a), we adopt an updated analytic prescription by Lehmer et al (2019), to estimate the total, 2-7 keV luminosity expected from XRBs (L gal XRB ). In particular, for a given stellar mass (M * , which scales with the LMXB population; Gilfanov 2004) and star formation rate (SFR, which scales with the HMXB population; Mineo et al 2012) the total, 2-7 keV luminosity from XRBs can be estimated (Lehmer et al 2019).…”
Section: Sdss J1448+1825mentioning
confidence: 99%